Characterization and phylogenetic analysis of the complete chloroplast genome of Carpesium longifolium F. H. Chen & C. M. Hu (Asteraceae, Inuleae) - Hui Chen; Tingyu Li; Xinyu Chen; Tianmeng Qu; Xinyi Zheng; Yueguang Wang; Liang Pang; Xianhua Gu; Zhixi Fu (Mitochondrial DNA. Part B. Resources)
In this study, we studied the complete chloroplast (cp) genome of Carpesium longifolium F. H. Chen & C. M. Hu 1974. The results indicated that the cp genome had a typical circular structure of 151,260 bp in length. A total of 127 genes were identified, including 36 tRNA genes, 8 rRNA genes and 83 protein-coding genes, with the GC content of 37.7%. Phylogenetic analysis revealed the systematic position of C. longifolium is sister to C. cernuum and C. faberi. For the identification and phylogenetics study of the genus, the chloroplast genome sequence of C. longifolium provides a useful genetic resource.